PENGARUH KUALITAS PELAYANAN PUBLIK TERHADAP KEPUASAN MASYARAKAT SUATU STUDI DI KELURAHAN KAIRAGI WERU KECAMATAN PAAL DUA KOTA MANADO - Kowimbin, Yoost Youke; Tulusan, Femmy; Kiyai, Burhanuddin (Sam Ratulangi University, 2017)
Abstract : Public Service delivery is still faced with the government system that has not been effective and efficient and the quality of human resources inadequate. This can be seen from the many complaints and complaints from the public either directly or through the mass media, such as complicated procedures, no certainty of the settlement period, the costs incurred, the requirements are not transparent, the attitude of the officers who are less responsive. And so on: thus generating a less favorable image of the government. As is the case with most, that the level of ease of service, especially for the middle to lower class, is still very low.This research is located in Kairagi Weru subdistrict, Paal District 2 Manado City, while the purpose of this research is to know how the performance of State Organizer in improving public service by using performance indicators proposed by Kotler (in Supranto, 1997: 561), this research type is research Diagnostic analytic design and analytical descriptive method with quantitative approach. The main instrument used to capture primary data in quantitative research is' questionnaire '' with interview guide through survey method and direct observation.The results showed that the five indicators used to measure the performance of the kelurahan government are: Reliability, Responsiveness, Confidence, Empaty, Tangible, influential significant to the level of community satisfaction, but after the analysis using Forward method, it turns out only four dimensions, namely reliability, Responsiveness, belief and empathy have a dominant effect on the satisfaction of the service users, especially in weru kairagi, sub-district of Manado city.It is concluded that the need of coaching and motivation to urban village apparatus in improving the quality of public service with some dimension of responsiveness and empathy have not reached optimally.Keywords: Prioritize the improvement of public service quality optimally and efficiently